Sustainable Smart Cities: A Fog Computing Framework for a Smart Urban Transport Network - Neagu, Ioan Mădălin (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
In the present paper, a fog computing framework for smart urban transport is developed. The proposed framework is adapted to the smart city concept. It uses a collaborative multitude of end-user clients to carry out a substantial amount of communication and computation. It can be adapted for specific situations of smart cities in Romania, such as: Cluj-Napoca, Timișoara, Iași or Bucharest. Economic and social implications as well as available European funding sources are presented.